2015
DOI: 10.5539/res.v7n4p93
|View full text |Cite
|
Sign up to set email alerts
|

Formation of University Students’ Readiness for Parenthood

Abstract: Forming students' readiness for family life involves the formation of their readiness for responsible parenthood. The aim of the study was the theoretical basis and experimental testing of the training program to form the students' readiness for parenthood. The article deals with the relevance of the problem, defining parenting in psychological, educational, social and philosophical literature, the study of the problem in Russia, research methodology and experimental study on the issue. During the research we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…In her work, Biktagirova and Valeeva (2015) note that the formation of students' readiness for family life is associated with the formation of their readiness for responsible parenthood. The study experimentally confirmed the effectiveness of the developed program "I am the Future Parent" for the formation of students' readiness for parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…In her work, Biktagirova and Valeeva (2015) note that the formation of students' readiness for family life is associated with the formation of their readiness for responsible parenthood. The study experimentally confirmed the effectiveness of the developed program "I am the Future Parent" for the formation of students' readiness for parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…The issue connected with the coeducation of children with special educational needs and children without health problems has acquired more and more attention in the last few years and obtained the name inclusive. It is recognized by the world community as the most humane and efficient as it grants the right for education to everyone irrespective of compliance with or discrepancy to school system criteria; besides, it promotes the expansion of all children's personal opportunities; it helps to develop such qualities as humanity, tolerance, readiness to help (Rieser, 2013;Valeeva & Demakova, 2015;Biktagirova & Valeeva, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These questions were investigated in the studies of Biktagirova (2013) and Biktagirova & Valeeva, (2015), Gasparyan (2009), Gurko (2003), Kharchev (2003, and others.…”
Section: Problem Statementmentioning
confidence: 99%